Navigating the Double-Edged Sword of AI Integration in Higher Education: Student perspective - Hashemi, Sylvana Sofkova; Lundin, Mona; Lantz-Andersson, Annika (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Digitalization is rapidly transforming society and reshaping higher education. Driven by generative AI technologies (GenAI), this shift challenges traditional paradigms and requires exploration of how digital literacy supports Reflective Practice-based Learning (RPL). Drawing on a sociomaterial theoretical understanding, this case study explores challenges and solutions in the dynamic interplay between social and material elements as AI is woven into the students’ study practices. The aim is to generate insights into students’ perspectives on the use of GenAI in their study practices. International master’s students in Swedish higher education participated in focus group interviews, reflecting on AI’s role in their education. Using a problem-tree methodology, students discussed the focal problems, the underlying causes, and possible solutions. Findings show that while students value GenAI for efficiency and judgement-free support, its ubiquity creates a perceived obligation to adopt it, which fuelling ethical, emotional, and academic tensions. Students fear diminished critical thinking and creativity through over-reliance, describing AI as both enabler and threat. They call for compulsory AI-use labelling by tool providers, explicit institutional guidelines, and more hands-on, creative assignments that foster independent reasoning and AI literacy. Without such measures, comfort, social pressure, and “speed culture” risk undermining RPL’s reflective depth. The study underscores the need for balanced, transparent integration of GenAI to harness its benefits without compromising core academic skills.